2021
DOI: 10.1002/clc.23745
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz, dysrhythmia and HIV

Abstract: To the EditorWe would like to share ideas on "Association between exposure to Efavirenz and substrates of dysrhythmia in HIV-infected young adults." 1 Hosseini et al. concluded, "patients with Efavirenz had higher prevalence of frequent PVC, frequent PAC, total significant dysrhythmia, Low HRV and prolonged QTc than controls." 1 The Efavirenez is widely mentioned for effect on cardiac rhythm. An important determinant is underlying genetic factors. CYP2B6*6*6 allele carrier is associated with cardiac rhythm pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…To the Editor, We appreciate Dr. Rujittika Mungmunpuntipantip and Dr. Viroj Wiwanitkit for their valuable comment about our article. 1 We found that chronic exposure to efavirenz (EFV) may be associated with increased premature ventricular contraction (PVC), premature atrial contraction (PAC) as well as decreased heart rate variability (HRV) in young human immunodeficiency virus (HIV) patients. 2 The impact of underlying genetic risk factors on the development of dysrhythmias has been partially understood.…”
mentioning
confidence: 99%
“…To the Editor, We appreciate Dr. Rujittika Mungmunpuntipantip and Dr. Viroj Wiwanitkit for their valuable comment about our article. 1 We found that chronic exposure to efavirenz (EFV) may be associated with increased premature ventricular contraction (PVC), premature atrial contraction (PAC) as well as decreased heart rate variability (HRV) in young human immunodeficiency virus (HIV) patients. 2 The impact of underlying genetic risk factors on the development of dysrhythmias has been partially understood.…”
mentioning
confidence: 99%